KOMPOSISI DAN STUKTUR VEGETASI RIPARIAN PADA TAMAN WISATA ALAM (TWA) BULUHCINA SEBAGAI SUMBER RANCANGAN MODUL MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Husna, Rizqa Alfajri; Yustina, Yustina; Nursal, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This research was conducted to determine the composition and structure of riparian vegetation at Natural Tourism Park(TWA) ) Buluhcina designed the biodiversity concept module on class X biodiversity material in April 2019-July 2019.This research was carried out in 3 stages, namely the field of data collection, the laboratory activity and the module design stage, the first stage was carried out at 4 observation locations located in the Nature Tourism Park (TWA) BuluhcinaThe research data was collected using a sample map (plot) consisting of 3 plots. The second phase of laboratory activities consisted of identifying plants and making herbaria. The third stage is module design using the ADDIE development model. The riparian vegetation composition of TWA Buluhcina saplings strata consists of 37 individuals, 10 species and 9 tribes. The highest importance index was Litsea noronhae (81.6%), with a diversity index between 0.63-2.16. Strata pole consists of 56 individuals, 9 types and 8 tribes. The highest importance index is Sterculia gliva (69.7%), with a diversity index between 1.05-2.12. As for the tree level, it consists of 145 individuals, 14 species and 12 tribes. The highest importance index is Gluta renghas (66.46%), with an index of diversity between 1.05-2.01.The research location is arranged by a type of vegetation that is evenly distributed with a dominance index in the range of 0.1-0.4.The results of the study can be used as a source of module design for biodiversity material in class X SMAKeyWords: Composition of Species, Vegetation Structure, Module